Factors Affecting Commodity Transfer Coffee Plants Become Vegetable Plants (Case Study of Masalle Village, Masalle District, Enrekang Regency) - Riska Handayani; Idrus Salam; La Ode Kasno Arif (International Journal of Technology and Education Research, 2023)
This study aims to 1) determine the types of plants cultivated by farmers after switching from coffee plants in Masalle Village, Masalle District, Enrekang Regency, and 2) determine the factors that influence the conversion of coffee plant commodities to vegetable crops in Masalle Village, Masalle District, Enrekang Regency. This research was conducted from January to February 2022. The population in this study were all farmers who converted commodities from coffee to vegetable crops, namely 30 farmers. The determination of the sample was carried out by census where the entire population was used as the research sample so that the number of samples in this study totaled 30 farmers who had transferred commodities from coffee plants to vegetable crops. Data were analyzed using qualitative descriptive analysis. Qualitative descriptive methods regarding situations and events, and used multiple linear regression analysis to describe the effect of the independent variables on the dependent variable. The results showed that 1) there were four types of vegetable commodities cultivated by farmers in Masalle Village, Masalle District, Enrekang Regency after switching from coffee farming, namely tomato plants (33.33%), cabbage plants (26.67%), chili plants (23 .33%), and shallots (16.67%), and 2) the factors that influence the transfer of commodities from coffee plants to vegetable crops indicate that the price variable has no significant effect on the commodity transfer with a significance value of the price variable (X1) of 0.080 or > and used multiple linear regression analysis to describe the effect of the independent variables on the dependent variable. The results showed that 1) there were four types of vegetable commodities cultivated by farmers in Masalle Village, Masalle District, Enrekang Regency after switching from coffee farming, namely tomato plants (33.33%), cabbage plants (26.67%), chili plants (23 .33%), and shallots (16.67%), and 2) the factors that influence the transfer of commodities from coffee plants to vegetable crops indicate that the price variable has no significant effect on the commodity transfer with a significance value of the price variable (X1) of 0.080 or > and used multiple linear regression analysis to describe the effect of the independent variables on the dependent variable. The results showed that 1) there were four types of vegetable commodities cultivated by farmers in Masalle Village, Masalle District, Enrekang Regency after switching from coffee farming, namely tomato plants (33.33%), cabbage plants (26.67%), chili plants (23 .33%), and shallots (16.67%), and 2) the factors that influence the transfer of commodities from coffee plants to vegetable crops indicate that the price variable has no significant effect on the commodity transfer with a significance value of the price variable (X1) of 0.080 or >α(0.05). Swhile the income and production variables have a significant effect on commodity transfer with a significance value of the income variable (X2) of 0.019 <α (0.05), while the production variable (X3) has a significance value of 0.039 <α (0.05).